Oar inertia forces - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
This article examines the oar inertia forces in rowing. An oar changes direction quite rapidly at the catch and finish, which means it moves with angular acceleration and generates inertia forces. The handle force increases at the end of recovery phase, before the catch. The higher the stroke rate, the higher acceleration and inertia forces ...